Quantitative determination of erlotinib in human serum using competitive enzyme-linked immunosorbent assay - Yuta Yamamoto; Tetsuya Saita; Yutaro Yamamoto; Masashi Shin (Elsevier, 2018)
A selective and sensitive competitive enzyme-linked immunosorbent assay (ELISA) method was developed and validated for the quantification of erlotinib in 50 µL of samples of human serum. Anti-erlotinib serum was obtained by immunizing mice with an antigen conjugated with bovine serum albumin and 3,4-bis(2-methoxyethoxy)benzoic acid using the N-succinimidyl ester method. Enzyme labeling of erlotinib with horseradish peroxidase was similarly performed using 3,4-bis(2-methoxyethoxy)benzoic acid. A simple competitive ELISA for erlotinib was developed using the principle of direct competition between erlotinib and the enzyme marker for anti-erlotinib antibody, which had been immobilized on the plastic surface of a microtiter plate. Serum erlotinib concentrations lower than 40 ng/mL were reproducibly measurable using the ELISA. This ELISA was specific to erlotinib and showed very slight cross-reactivity (6.7%) with a major metabolite, O-desmethyl erlotinib. Using this assay, drug levels were easily measured in the blood of mice after oral administration of erlotinib at a single dose of 30 mg/kg. ELISA should be used as a valuable tool for therapeutic drug monitoring and in pharmacokinetic studies of erlotinib. Keywords: Erlotinib, Enzyme-linked immunosorbent assay, O-desmethyl erlotinib, Tyrosine-kinase inhibitor